Theoretical and Legal Bases of Artificial Intelligence Punishment System Development - Rustamovich Gaifutdinov, Ramil (2020)
The article discusses the problematic aspects of artificial intelligence technology application. The author's classification of artificial intelligence types is proposed, depending on their material expression (artificial intelligence unit, artificial intelligence carrier and artificial intelligence). The study allowed us to form the theoretical and legal foundations of artificial intelligence punishment system development. The authors proposed the types of artificial intelligence punishments and described their essence. To such types of punishments, they include complete deactivation (destruction) of artificial intelligence; partial deactivation of artificial intelligence; confiscation of artificial intelligence in favor of the state;the prohibition of artificial intelligence use in certain fields of activity; the implementation of gratuitous activities by artificial intelligence in the interests of the state or society; provision of a convict status (unreliable) for artificial intelligence.